Advancing Understanding of Anorectal Malformations Through Microfocus Computed Tomography Imaging of Resected Material - Daniël Docter; Bernadette S. de Bakker; Jaco Hagoort; Joris J.T.H. Roelofs; Sjoerd de Beer; Ernst van Heurn; Joep Derikx; Marc A. Benninga; Justin de Jong; Ramon R. Gorter (Gastro Hep Advances)
Background and Aims: Patients born with anorectal malformations (ARMs) might experience constipation and fecal incontinence. During ARM surgery (anterior and posterior sagittal anorectoplasty procedure), the distal part of the bowel (fistula) is usually resected. Microfocus computed tomography (micro-CT) imaging, capable of imaging samples in ultra-high 3-dimensional resolution, can be used to learn from this resected material. Through this technique, we aim to investigate whether or not structures, such as the internal anal sphincter (IAS), are present within this fistula. Methods: Pediatric patients undergoing surgical reconstruction for ARM were eligible for inclusion. Resected fistulas were fixed using 4% paraformaldehyde and stained with 3.75% B-Lugol for 48 hours to improve soft tissue contrast. Scans were performed on a Phoenix Nanotom micro-CT with a voxel size between 4–6 μm. Samples were destained for subsequent histopathological examination. Outcomes were presence of structures like the IAS, epithelial transition zone and ganglia. ARM fistulas were compared with a fetal anal canal sample derived from the Dutch Fetal Biobank. Results: Eleven ARM fistulas were analyzed. All samples showed evidence of normal development of the rectal wall. Columnar epithelium and stratified squamous epithelium were observed. Muscle fibers were present, arranged in circular pattern that expanded toward the distal end, becoming the intrinsic sphincter (IAS). Ganglia were present with normal appearance. Conclusion: We present micro-CT imaging to research resected material to provide new insights in microscale anatomy. The fistula, currently resected during surgical reconstruction for ARM, contains vital structures like the IAS, normal epithelial transition zone and normal ganglion cells. Although clinical functionality should be studied in the future, our results indicate that the fistula has a normal anal canal morphology and should be spared during ARM reconstruction if possible.